Social Movement on Social Media: #TolakPengesahanRKUHP and #ReformasiDikorupsi - Saputri, Rivi; Mutiarin, Dyah; Sukarno, Mohamad (Nyimak: Journal of Communication, 2024)
This study aims to determine the social movements in social media in #TolakPengesahanRKUHP and #ReformasiDkorupsi. The two hashtags are trending on social media in the discourse of denying the ratification of the RKUHP. The research method uses qualitative analysis using Computer Assigned Qualitative Data Software (CAQDS) Nvivo 12plus. The research data is then visualized through crosstab analysis and word cloud analysis. The results showed that #TolakPengesahanRKUHP has the highest intensity in society with an anti-criticism democratic narrative and a series of articles that interfere with citizens’ privacy. The two action groups promoted by YLBHI, Direct Action, PBHI, and FRI with guidance, do not have legal certainty and perpetuate corruption. There was no response at all from the government element to the discourse. The second hashtag, #ReformasiDikorupsi the highest intensity in the community with the tagline “Motion of No Confidence” over the government and the House. The action group represented by YLBHI, LBH Surabaya, and the student community expressed criticism of the silencing of democracy for the people. In addition to the rejection of the RKUHP, several other regulations were also reviewed, such as the KPK Law, the Criminal Code Bill, the Revision of the Manpower Law, the Water Resources Law, and others. Then from the government element based on #ReformasiDikorupsi, there are no responses to this discussion, only shared by orderly demonstrations without disturbing public order.Keywords: RKUHP, social movement, #TolakPengesahanRKUHP, #ReformasiDikorupsiABSTRAKPenelitian ini bertujuan untuk mengetahui social movement dalam social media pada #TolakPengesahanRKUHP dan #ReformasiDkorupsi. Dua hastag tersebut trending dalam sosial media dalam diskursus penolakan pengesahan RKUHP. Metode penelitian menggunakan kualitatif dengan analisis menggunakan Computer Assigned Qualitative Data Software (CAQDS) Nvivo 12plus. Data penelitian kemudian divisualisaikan dalam bentuk crosstab analysis dan words cloud analysis. Hasil penelitian menunjukan #TolakPengesahanRKUHP memiliki intensitas tertinggi pada masyarakat dengan narasi demokrasi anti kritik dan sederet pasal yang menganggu privasi warga negara. Kedua kelompok aksi yang dipelapori oleh YLBHI, Aksi Langsung, PBHI, dan FRI dengan tuntunan tidak memiliki kepastian hukum serta melanggengkan korupsi. Kemudian dari elemen pemerintah, tidak ada sama sekali response atau tanggapan atas diskursus tersebut. Hastag kedua #ReformasiDikorupsi dengan intensitas tertinggi pada masyarakat dengan tagline “Mosi Tidak Percaya” atas pemerintah dan DPR. Kelompok aksi yang diwakili oleh YLBHI, LBH Surabaya, dan komunitas mahasiswa menyampaikan kritik pada pembungkaman demokrasi bagi rakyat. Selain penolakan RKUHP beberapa regulasi lainya juga dikaji seperti UU KPK, RUU KUHP, Revisi UU Ketenagakerjaan, UU Sumber Daya Air, dan lainnya.Kata Kunci: RKUHP, social movement, #TolakPengesahanRKUHP, #ReformasiDikorupsi